PENERAPAN ALGORITMA C4.5 PADA PRODUK PENJUALAN MAKANAN RINGAN - Rahmadayanti, Fitria; Asminah, Asminah; Cahaya, Della Tri (LPPM UNIVERSITAS BINA INSAN, 2024)
Advances in technology and information today create smart innovations in business, which we can call business intelligence. Competition in the business sphere forces business people to always think about strategies and breakthroughs that can ensure the sustainability of the business being run.The purpose of this study is to accurately analyze the C4.5 algorithm in classifying the best-selling food sales products. The results of research that have been obtained that product sales that are less than 207 include food that is less in demand while sales of products that are more than 207 are among the best-selling foods. Product sales of more than 207 are the best-selling foods where there are 5 best-selling food products. While the sales of products that are less than 207 are less in demand food where there are 5 food products that are less in demand.